Bamboo NiR gene is associated with regeneration capacity. Issue 2 (4th March 2018) - Guo, Xiaomei; Ji, Lifen; Zhu, Longfei; Song, Liling; Liu, Shinan; Zang, Qiaolu; Lin, Xinchun
ABSTRACT: It was reported that the activity of NiR (nitrite reductase) enzyme encoded by the NiR gene was correlated with the regeneration ability in rice. To testify the function of NiR gene in bamboo, seven bamboo species whose calli had different differentiation rate were chosen to analyse their NiR enzyme activity. The results showed that bamboo NiR enzymatic activity had a certain correlation with the regeneration capacity. A NiR gene named DhNiR from Dendrocalamus hamiltonii with high regeneration capacity was cloned. Sequence analysis revealed that the ORF of DhNiR was 1779bp encoding 592 amino acids. Overexpression of DhNiR in rice reduced the time of shoot differentiation and increased the transformation rate, suggesting that DhNiR might play an important role in the regeneration ability of bamboo, and can be applied in regeneration and gene transformation of bamboo and other plant species.